Penatalaksanaan Kasus Skizoafektif Tipe Depresi pada Ny. SH Usia 44 Tahun dengan Pendekatan Kedokteran Keluarga - Nadya Marshalita; Cahyaningsih Fibri Rokhmani (MAJORITY, 2021)
Schizoaffective disorder is a chronic mental disorder characterized by psychotic and mood symptoms. Psychotic disorders became the top 10 most common diseases at the Gedong Air Community Health Center in the course of January - June 2021 with a prevalence of 4.05%. A proper and holistic treatment using family medicine approach is required to improve the patient's quality of life. This study is a descriptive study of case reports. Primary data were obtained through autoanamnesis and alloanamnesis, mental status examination, and home visits. Secondary data were garnered from the patient's medical record. Patient Mrs. SH, 44 years old, complained of sleeping difficulty during night since 2 months ago followed by frequent soliloquies, asociality, fatigue, auditory hallucination, visual hallucination, and sense of foreshortened future. Clinically, the patient was diagnosed with schizoaffective depressive type (ICD-10 F25.1; ICPC-2:P98). The patient received medical treatment in the form of antidepressants, second-generation antipsychotics, anticholinergics, and phenothiazine antipsychotics. Patients also received interventions in the form of invitations to socialize, write diaries, and paint, as well as education using poster media. The authors conducted an evaluation 16 days post-intervention. The patient became more aware of her disease and had better behavior changes that affected the success of therapy. Patients with schizoaffective depressive type require holistic management with family medicine approach to support the success of therapy and improve the patient's quality of life.